Intra/Inter-Particle Energy Transfer of Luminescence Nanocrystals for Biomedical Applications. (5th June 2012) - Liu, Ching-Ping; Cheng, Shih-Hsun; Chen, Nai-Tzu; Lo, Leu-Wei
Abstract : Elaborate design of energy transfer systems in luminescent nanocrystals revealed tremendous advantages in nanotechnology, especially in biosensing and drug delivery systems. Recently, upconversion nanoparticles have been discussed as promising probes as labels in biological assays and imaging. This article reviews the works performed in the recent years using quantum dot- and rare-earth doped nanoparticle-based energy transfer systems for biomedical applications.